Use of Mg-Al/hydrotalcite Catalyst in Biodiesel Production from Avocado Seed Oils: A Preliminary Study - Irvan Maulana Firdaus; Tri Fitriany; Milda Nurul Hidayah; Agus Soleh; Khilman Husna Pratama; Febiyanto Febiyanto (Research Center for Chemistry - LIPI, 2019)
Biodiesel production of avocado seed oils has been carried out using the heterogeneous catalyst of Mg-Al/hydrotalcite. Transesterification process was conducted by varying temperature reaction and oil-methanol molar ratio. The reaction temperature was 30, 40, 50, and 60°C, whereas the oil-methanol molar ratio was 1:3, 1:6, 1:9, and 1:12, respectively. As-synthesized Mg-Al/hydrotalcite catalyst was characterized using X-ray diffraction and FTIR. Meanwhile, the biodiesel was analyzed their density, viscosity, water content and 1H-NMR analysis. The results showed that optimum condition in biodiesel production was oil-methanol molar ratio of 1:6 at a reaction temperature of 60°C for 60 minutes and catalyst quantity of 2% yielding biodiesel conversion percentage was approximately 15.90%. However, this preliminary findings showed that Mg-Al/hydrotalcite was able to convert the avocado seed oils into biodiesel even if still need further analysis and research so that produces a higher percentage of biodiesel conversion.